2011
DOI: 10.1007/s11243-011-9513-z
|View full text |Cite
|
Sign up to set email alerts
|

Tri-p-tolylphosphine-cyclopalladated ferrocenylpyrimidine complexes: synthesis, crystal structures, catalytic activity, and a palladacycle cocrystallization adduct

Abstract: Two new tri-p-tolylphosphine-cyclopalladated ferrocenylpyrimidine complexes 1 and 2 have been prepared in good yields by reaction of the corresponding chloride-bridged palladacyclic dimers 1a and 2a with tri-ptolylphosphine. Complexes 1 and 2 were characterized by elemental analysis, IR, 1 H NMR, and ESI-MS. Additionally, their crystal structures have been determined by X-ray diffraction, and intermolecular C-HÁÁÁCl hydrogen bonds were found in their crystals. Complex 1 was found to be a palladacycle cocrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, 1 could be present in lower than 1 mol‐% without loss of activity (Entry 5), however, the yield of 2 only reached 18 % when 0.1 mol‐% of 1 was used (Entry 6), which revealed that a small percentage (less than 0.1 mol‐%) of 1 behaves as the catalyst11 and the remaining 1 behaves as the substrate. The results indicated that 1 was an efficient precatalyst 10c. Loading naphthylboronic acid ( a ) to 4.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 1 could be present in lower than 1 mol‐% without loss of activity (Entry 5), however, the yield of 2 only reached 18 % when 0.1 mol‐% of 1 was used (Entry 6), which revealed that a small percentage (less than 0.1 mol‐%) of 1 behaves as the catalyst11 and the remaining 1 behaves as the substrate. The results indicated that 1 was an efficient precatalyst 10c. Loading naphthylboronic acid ( a ) to 4.0 equiv.…”
Section: Resultsmentioning
confidence: 99%